PENGARUH CAPITAL ADEQUACY RATIO (CAR) DAN BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) TERHADAP KINERJA BANK SYARIAH - Uum Helmina Chaerunisak; Dewi Kusuma Wardani; Zara Tri Prihatiningrum (Universitas Mataram, 2019)
This study aims to determine the effect of capital adequacy ratio, financing to deposite ratio and operating costs of operating income on healthy returns on. This study uses data which is a time series cross section data from sharia banking statistics from 2015-2018 and 2019 (only January to August because the most recent data) is registered with Otoritas Jasa Keuangan (OJK). Data collection methods in this study used purposive sampling. Analysis of the data used is multiple linear regression. The classic assumption tests used in this study are the normality test, the multicollinearity test, the heteroscedasticity test, and the autocorrelation test. The results of this study indicate that the capital adequacy ratio does not affect the return on assets, operational costs of operating income negatively affect the return on assets.